Penyususan Draf Modul Kesiapsiagaan Bencana Melalui Pendekatan Focus Group Discussion - Suparji Suparji; Nani Surtinah; Susi Milwati; Farida Halis; Emy Rianti; Heru Santoso Wahito Nugroho; Aris Handayani (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
In an effort to increase community capacity, especially knowledge and attitudes about disaster preparedness, it is necessary to optimize. Therefore the development of teaching materials in the form of modules is a very urgent need. In order to develop good modules that are in accordance with the needs of the community, a needs analysis step is needed based on the real conditions that exist in the community. A good module is a module that can condition learning activities in the community to be more well-planned, independent, thorough and with clear results (outputs). The purpose of this research was to design a module through needs analysis in preparing a draft disaster preparedness module through a Focus Group Discussion approach, so that a good module is produced. The method used in this study was Research and Development with steps that had been implemented including analysis of the needs of teaching materials through Focus Group Discussion activities, and good module drafts are produced as a basis for preparing disaster preparedness modules. Participants in the FGD activities were representatives of members of the DESTANA DRR forum in four villages in the Poncol District area. 40 people, DESTANA forum facilitators 2 people and 2 disaster practitioners. The data collection method uses FGD activities. The FGD implementation process was designed through several stages, namely determining objectives, number of participants, implementation time, length of implementation, FGD topics and a list of questions that need to be discussed in FGD activities regarding the framework of the disaster preparedness module. The results of the FGD based on strategic issues as the basis for drafting the preparedness module draft agreed that there were 5 module chapters, namely integrated knowledge and attitude variables on disaster management concepts, policies and guidelines, emergency response plans, early warning systems, and human resource mobilization. The conclusion from the FGD results was the drafting of a community-based disaster preparedness module based on the development of the strategic issues discussed in the FGD activities. The strategic contents include integrated knowledge and attitude variables regarding the concept of disaster management, policies and guidelines, emergency response plans, early warning systems, and HR mobilization.Keywords: focus group discussion; module; disaster preparedness ABSTRAK Dalam upaya peningkatan kapasitas masyarakat terutama pengetahuan dan sikap tentang kesiapsiagaan bencana perlu untuk dioptimalkan. Oleh karena itu pengembangan bahan ajar dalam bentuk modul menjadi kebutuhan yang sangat mendesak. Untuk menyusun modul yang baik dan sesuai dengan kebutuhan masyarakat diperlukan langkah analisis kebutuhan berasarkan kondisi riil yang ada di masyarakat. Modul yang baik adalah modul yang dapat mengkondisikan kegiatan pembelajaran dimasyarakat lebih terencana dengan baik, mandiri, tuntas dan dengan hasil (output) yang jelas. Tujuan penelitian ini adalah merancang modul melalui analisis kebutuhan dalam penyususan draf modul kesiapsiagaan bencana melalui pendekatan Focus Group Discussion, supaya dihasilkan modul yang baik. Metode yang digunakan dalam penelitian ini adalah pengembangan (Research and Development) dengan langkah-langkah yang telah dilaksanakan meliputi analisis kebutuhan bahan ajar melalui kegiatan Focus Group Discussion, dan dihasilkan draf modul yang baik sebagai dasar penyusunan modul kesipsiagaan bencana. Partisipan dalam kegiatan FGD adalah perwakilan dari anggota forum PRB DESTANA di empat desa di wilayah Kecamatan Poncol. berjumlah 40 orang, fasilitator forum DESTANA sebanyak 2 orang dan praktisi  bencana sejumlah 2 orang. Metode pengumpulan data menggunakan melalui kegiatan FGD. Proses peelaksanaan FGD dirancang melalui beberapa tahapan yaitu menentukan tujuan, jumlah partisipan, waktu pelaksanaan, lama pelaksanaan, topic FGD serta daftar pertanyaan yang perlu dibahas dalam kegiatan FGD tentang kerangka modul kesiapsiagaan bencana. Hasil FGD berdasarkan isu strategis sebagai dasar penyusunan draf modul kesiapsiagaan disepakati ada 5 bab modul yaitu variabel pengetahuan dan sikap yang terintegrasi tentang konsep manajemen kebencanaa, kebijakan dan panduaan, Rencana tanggap darurat, sistem peringatan dini, dan mobilisasi SDM. Kesimpulan dari hasil FGD adalah tersusunya draf modul kesiapsiagaan bencana berbasis masrakat berdasarkan pengembangan dari issu strategis yang dibahas dalam kegiatan FGD. Issi strategis tersebut meliputi variabel pengetahuan dan sikap yang terintegrasi tentang konsep manajemen kebencanaa, kebijakan dan panduaan, rencana tanggap darurat, sistem peringatan dini, dan mobilisasi SDM.Kata kunci: focus group discussion; modul; kesiapsiagaan bencana